CONSUMER BUYING BEHAVIOUR TOWARDS ONLINE SHOPPING: AN EMPIRICAL STUDY WITH REFERENCE TO LUCKNOW CITY, INDIA - Dr Geetika Tandon Kapoor, Ashish Gupta, Esha Dhawan (Chelonian Research Foundation, 2023)
With the tremendous growth in retail marketing and increased internet penetration in the economy, there had been an exponential change in the way of shopping by the customers in India. Apart from traditional way of shopping, consumers are also preferring online shopping due to easy access to internet service, convenience in usage and variety of products availability. Keeping in mind the primary goal of offering goods and services to serve customers’ needs & survive competition, e-retailers wants to analyse customers behaviour, preferences and expectations regarding online shopping. The present study aims towards analysing consumers behaviour towards online shopping. Sample is collected through a structured questionnaire from 154 respondents. Random sampling is used for sample identification having respondents belonging to different gender, age groups, income, professions. Data is analysed by using tables, graph, charts, percentage and ANOVA etc. The study will provide e-retailers useful insight for developing marketing strategies regarding consumers likings, disliking and preferences towards online shopping. Keywords: Online shopping, consumer buying Behaviour, Internet, Customer satisfaction.